PENGARUH KEPUTUSAN INVESTASI DAN KEBIJAKAN DEVIDEN YANG DI MEDIASI OLEH VARIABEL RISIKO TERHADAP NILAI PERUSAHAAN STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - Ruth Siregar; Yulia Efni; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine direct and indirect effect ofinvestment decision and dividend policy, business risk and firm value.Furthermore inderect effect on examined with testing investment decision and dividend policyon firm value mediated by business risk. Purposive sampling is use to get our samples from fifty-four firms population that include in miscellaneous industry. We get twenty-one firms that used as our samples to analysis the data we use path analysis. The results of this study indicate that direct investment decision no significant effect on the business risk, dividend policy no significant effect on business risk directly. Direct investment decision no significant effect on the firm value, dividend policy directly significant effect on firm value. Direct business risk had significant effect on firm value. This means that the business risk is not able to mediate the relationship between investment decision on firm value And business risk are also not able to mediate relationship between the dividend policy condition on the firm value.Keywords:Investment Decision, Dividend Policy, Business Risk, and Firm Value